2007
DOI: 10.1590/s0004-282x2007000400014
|View full text |Cite
|
Sign up to set email alerts
|

Lexical semantic memory in amnestic mild cognitive impairment and mild Alzheimer's disease

Abstract: -Objective: To study lexical semantic memory in patients with amnestic mild cognitive impairment (aMCI), mild Alzheimer's disease (AD) and normal controls. Method: Fifteen mild AD, 15 aMCI, and 15 normal control subjects were included. Diagnosis of AD was based on DSM-IV and NINCDS-ADRDA criteria, and that of aMCI, on the criteria of the International Working Group on Mild Cognitive Impairment, using CDR 0.5 for aMCI and CDR 1 for mild AD. All subjects underwent semantic memory tests (Boston Naming-BNT, CAMCOG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
0
14
0
4
Order By: Relevance
“…Many studies have demonstrated the utility of the BNT in distinguishing between late stage AD and age-related decline [5-7]. More recent studies of the BNT in the context of normal aging, MCI, and AD populations have repeatedly shown MCI patients performing normally or similar to age-matched controls on the BNT [8, 9]. These data suggest that while the BNT has utility in normal aging and distinguishing normal aging from AD, it has less utility in identifying MCI.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the utility of the BNT in distinguishing between late stage AD and age-related decline [5-7]. More recent studies of the BNT in the context of normal aging, MCI, and AD populations have repeatedly shown MCI patients performing normally or similar to age-matched controls on the BNT [8, 9]. These data suggest that while the BNT has utility in normal aging and distinguishing normal aging from AD, it has less utility in identifying MCI.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly individuals with MCI show poor performance on semantically demanding tasks [26,29,31]. The relationship between the performance on semantically demanding tasks and the naming accuracy rate suggests semantic deficits in MCI.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the performance on semantically demanding tasks and the naming accuracy rate suggests semantic deficits in MCI. First, poor semantic ability, as assessed by semantic categorization, was significantly associated with the accuracy rate in the BNT in patients with MCI [26]. Second, individuals with MCI performed more poorly on semantic verbal fluency tests than on phonemic verbal fluency tests [29,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O Teste de Aprendizagem Auditivo-Verbal de Rey (RAVLT) tem se mostrado útil na avaliação da memória de idosos [1][2][3][4] , contribuindo particularmente para o diagnóstico diferencial entre o envelhecimento normal e quadros demenciais como a demência do tipo Alzheimer [5][6][7] . O teste é utilizado para avaliação da memória e aprendizagem 8 , sendo considerado um instrumento sensível ao déficit de memória episódica 2,5,9 .…”
Section: Introductionunclassified